An Experiment in the Measurement of Business Motivation - Meyer, John R. (The Review of Economics and Statistics, 1967)
D OUBTS have increasingly beset economists regarding the serviceability of the simplification known as economic man in explaining behavior. rise of the large corporation is unquestionably the biggest single contributor to this uneasiness. There is suspicion that a divorce of ownership and control leads to corporation growth, continuity and survival often taking precedence over pure profit maximization in the subjective preference scales or objectives of professional managements.' In essence, it is suggested that seeks a multiplicity of goals rather than only the goal of profits. Business firms with different goals may, of course, desire different relationships between recorded measures of performance. To take an extreme example, let the relationship between investment and sales be defined by one of two objectives: (1) minimizing costs by achieving optimal capacity-output relationships; and (2) obtaining as large a share of the market as possible. In both cases, a positive relationship between sales changes and investment might be expected when sales are increasing, though not necessarily of equal amounts. However, in case (1) as sales decrease, investment would also decrease, everything else equal. By contrast, in case (2) as sales decline (everything else equal, including the sales of competitors), investment could increase. Case (1), of course, is a form of the acceleration principle at the micro level while case (2) implies that the zest or need to keep pace with competitors or to maintain a market share will be registered even under adverse conditions. Other, similarly contrary examples could be cited. For example, the relationship between the age of capital stock and the rate of investment might be expected in a world of multiple motivations to be either positive or negative. As the age of the capital stock increased, the rate of investment might also be expected to increase because there would be a more urgent need for new and more efficient productive capacity. Contrarily, old equipment might be a sign of business senility or overcaution.2 Thus, firms with old equipment might * This study is one part of a series of interrelated studies of corporate and financial policies under the overall direction of Professor John Lintner. These studies are financed under a grant of the Rockefeller Foundation to the Harvard Business School for work in the general area of profits and the functioning of the economy. Much of the drafting of this study was done while the author was on a Guggenheim Fellowship in the academic year 1958-1959 and a Ford Foundation Faculty Research Professorship during 1962-1963. All this support is most gratefully acknowledged. ' literature, pro, con, or neutral, on this subject is quite extensive. Among the more recent and notable contributions (but hardly an exhaustive listing) are: W. J. Baumol, Business Value, and Growth (New York: Macmillan, 1959); A. A. Berle, The Impact of the Corporation on Classical Economic Theory, Quarterly Journal of Economics, LXXIX, No. 1 (Febr. 1965), 25-40; R. M. Cyert and J. G. March, Behavioral Theory of the Firm (Englewood Cliffs, N.J.: Prentice-Hall, 1963); C. Kaysen, Another View of Capitalism, Quarterly Journal of Economics, LXXIX, No. 1 (Febr. 1965), 41-51; R. Marris, Economic Theory of Capitalism (New York: Free Press of Glencoe, 1964); J. R. Monsen and A. Downs, A Theory of Large Firms, Journal of Political Economy, LXXIII, No. 3 (June 1965), 221-236; E. Penrose, Theory of the Growth of the Firm (Oxford: Blackwell, 1959); S. Peterson, Corporate Control and Capitalism, Quarterly Journat of Economics, LXXIX, No. 1 (Febr. 1965), 1-24; 0. E. Williamson, A Dynamic Theory of Interfirm Behavior, Quarterly Journal of Economics, LXXIX, No. 4 (Nov. 1965), 579-607. Two standard classics, that provoked much of the subsequent discussion, are: A. Berle and G. Means, Modern Corporation and Private Property (New York: Macmillan, 1932); and R. A. Gordon, Business Leadership in the Large Corporation (Washington: Brookings Institution, 1945, and Berkeley: University of California Press, 1961). more modern look at some of these same problems is to be found in J. K. Galbraith, New Industrial State (Boston: Houghton Mifflin, 1967). Finally, concise summaries and useful further bibliography can be found in C. A. Hickman, Managerial Motivation and the Theory of the Firm, American Economic Review, XLV (May 1955), 544-554; A. G. Papandreou, Some Basic Problems in the Theory of the Firm, in B. F. Haley, ed., Survey of Contemporary Economics, Vol. II (Homewood, Ill., 1952) and the comments by E. S. Mason and R. B. Heflebower therein; and R. B. Heflebower, The Firm in Oligopoly Analysis, Weltwertschaftliches Archio, 84 (1960), 150-164. 2 J. Meyer and E. Kuh, Investment Decision (Cambridge, Mass., 1957), ch. VI.